Model Penerapan Akuntansi Aset Desa: Mengurai Kompleksitas Permendagri No 1/2016 - Safira, Finna Dian; Amalia, Firda Ayu; Wicaksono, Agung Prasetyo Nugroho (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2024)
The purpose of this research is to analyze accounting records on village asset management based on Permendagri Number 1 of 2016 in Sendangagung Village, Plaosan District, Magetan Regency which discusses 12 (twelve) indicators of village asset management. This research uses qualitative research with a direct case study on the Sendangagung Village Government as a research object as well as an internship place from researchers where data is obtained through interviews and documentation. The results of the study stated that accounting records in asset management have not been carried out properly and optimally, where there are still some indicators that are not in accordance with the established regulations. The obstacle faced by the village is the lack of human resources so that the entrepreneurship process is not optimal other than that the asset inventory has not been carried out optimally. Efforts that can be made by the Village Government are the recruitment of experts who can help recording and reporting that cannot be done optimally by the device as well as the procurement of fostering the use of SIPADES by the District or Regency.